The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.toxrep.2021.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol and nicotine co-administration on follicular atresia and placental histo-morphology in the first-generation mice pups during intrauterine development and lactation periods

Abstract: Graphical abstract Schematic representation of experimental design in different groups of mothers and offspring. CTL group: control group; Veh group: vehicle group received normal saline; Ni group: nicotine group received 1 mg/kg/day nicotine, subcutaneously; EtOH group: ethanol group received 3 g/kg/day, 20 % v/v ethanol intraperitoneally; Ni + EtOH group: ethanol plus nicotine which received both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…Contrary to the present study, the primordial follicle numbers were reduced in nicotine-treated rats or mice [ 13 , 40 , 55 , 56 ]. These differences may arise from differences in species, animal age, duration of treatment, route of administration, and type of studies (in vivo or in vitro).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to the present study, the primordial follicle numbers were reduced in nicotine-treated rats or mice [ 13 , 40 , 55 , 56 ]. These differences may arise from differences in species, animal age, duration of treatment, route of administration, and type of studies (in vivo or in vitro).…”
Section: Discussioncontrasting
confidence: 99%
“…This study indicated the efficacy of PG, especially in the dose of 1 g/kg against apoptotic and oxidative damages of the ovary induced by nicotine. Fertility duration and women's health status depend on the reserves of ovarian follicles [ 40 ]. Follicle loss may be due to some mechanisms such as hormonal disturbances, ROS elevation, reduction of enzymatic and non-enzymatic antioxidants, the elevation of apoptotic markers, and proliferation index reduction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations